Respuesta :

Answer:

[tex]g\left(x\right)=x^3\:-\:4x^2\:-\:x\:+\:22[/tex] in the factored form will be:

  • [tex]g\left(x\right)=x^3-4x^2-x+22=\:\left(x+2\right)\left(x^2-6x+11\right)[/tex]

Step-by-step explanation:

Given the function

[tex]g\left(x\right)=x^3\:-\:4x^2\:-\:x\:+\:22[/tex]

Use the rational root theorem.

[tex]a_0=22,\:\quad a_n=1[/tex]

[tex]\mathrm{The\:dividers\:of\:}a_0:\quad 1,\:2,\:11,\:22,\:\quad \mathrm{The\:dividers\:of\:}a_n:\quad 1[/tex]

[tex]\mathrm{Therefore,\:check\:the\:following\:rational\:numbers:\quad }\pm \frac{1,\:2,\:11,\:22}{1}[/tex]

[tex]-\frac{2}{1}\mathrm{\:is\:a\:root\:of\:the\:expression,\:so\:factor\:out\:}x+2[/tex]

[tex]=\left(x+2\right)\frac{x^3-4x^2-x+22}{x+2}[/tex]

as

[tex]\frac{x^3-4x^2-x+22}{x+2}=x^2-6x+11[/tex]        ∵ [tex]x^3-4x^2-x+22=\left(x+2\right)\left(x^2-6x+11\right)[/tex]

so the expression becomes

[tex]x^3\:-\:4x^2\:-\:x\:+\:22=\left(x+2\right)\left(x^2-6x+11\right)[/tex]

Therefore,

[tex]g\left(x\right)=x^3\:-\:4x^2\:-\:x\:+\:22[/tex] in the factored form will be:

  • [tex]g\left(x\right)=x^3-4x^2-x+22=\:\left(x+2\right)\left(x^2-6x+11\right)[/tex]

                             

ACCESS MORE